Dynamics of free radical processes in the oral fluid of patients with chronic recurrent aphthous stomatitis at the first stage of therapy - O. V. Tarasova; A. V. Shumsky; O. N. Pavlova; O. N. Gulenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Chronic recurrent aphthous stomatitis (CRAS) is a disease of the oral mucosa, characterized by the appearance of specific round aphthous forms with hyperemic corolla, covered with grayish-yellow plaque against the background of inflamed mucous membrane, which violates the oxidative homeostasis of oral fluid and the body as a whole.The aim of our study was to reveal the dynamics of free radical processes in oral fluid of patients with chronic recurrent aphthous stomatitis on the background of the first stage of antiseptic therapy with analgesics in order to determine the optimal treatment tactics for this condition. In order to achieve the set objective we had to solve the following tasks: to evaluate the functional activity of free radical processes in the oral liquid of patients with CPAS on the background of antiseptics (chlorhexidine, octenisept, furacilin, myramistine) and anaesthetic (Camistad gel) application for 7 days.Materials and Methods. During the study the oral fluid of 120 people diagnosed with CPPS was studied, divided into 4 groups equally: Group 1 – control, patients used the antiseptic chlorhexidine for gargling; Group 2 – patients with CPPS therapy with octenisept; Group 3 – patients with CPPS therapy with furacilin; Group 4 – patients with CPPS therapy with miramistine. For pain relief, patients in all groups used Kamistad gel. Analysis of free radical processes in oral fluid of patients was carried out before the study and on the 7th day of therapy by determining products of oxidative modification of biomolecules on the basis of quantitative evaluation of stained complex with thiobarbituric acid (TBA), maximal flash (MVHL) and area (PCL) of H2O2-induced luminol-dependent chemiluminescence using LT-01 chemiluminometer ("Horos" "Joint Venture Soviet-Swedish Company"). Concentration of diene conjugates and malonic dialdehyde was also determined to estimate enzymatic part of oxidative homeostasis.Results of the study. Results of the researches permit to conclude that at chronic recurrent aphthous stomatitis enzymatic activity of an oral liquid changes. According to the presented data the initial values of concentration of TBK-RP, maximal flash of oral chemiluminescence, area of oral chemiluminescence and concentration of MDA and DC in the control group and three experimental groups reliably differ from the data received on the 7th day of the research. Significant decrease of the studied indexes of oral liquid testifies to the efficiency of the first stage of therapy of aphthous stomatitis by antiseptic preparations and decrease of intensity of oxidative processes in oral liquid. Of all the proposed antiseptics the best efficiency is demonstrated by octenisept, reliably worse are chlorhexidine and myramistine and the least effective in the therapy of CPAS is furacilin.Conclusions: treatment of CPAS with Octenisept in combination with Camistad gel is the most effective in restoration of the disturbed oxilite.